Pre-slaughter factors affecting mobility, blood parameters, bruising, and muscle pH of finished beef cattle in the United States - Sullivan, Paxton, author; Edwards-Callaway, Lily, advisor; Hess, Ann, committee member; Nair, Mahesh Narayanan, committee member (Colorado State University. Libraries, 2023)
Decades of work have focused on reducing fear, stress, and discomfort in cattle moving through the pre-slaughter phase by improving and promoting low-stress animal handling, transportation, and management processes. Even still, there is limited information about the effects of pre-slaughter factors on animal welfare and meat quality outcomes in finished cattle in the United States. The objective of this study was to track individual animals through the slaughter process to identify pre-slaughter factors associated with key welfare and quality outcomes. A total of 454 cattle from one slaughter facility were included in the study. Pre-slaughter factors assessed included: distance traveled, lairage density, lairage duration, season, and truck waiting time. Animal-related characteristics, i.e., body weight, breed, and sex, were also recorded. One trained observer scored mobility of all study cattle using the North American Meat Institute's 1-4 scale (i.e., normal to extremely reluctant to move). Postmortem, exsanguination blood was collected on animals and analyzed for cortisol, creatine kinase, and lactate. Carcass bruising was scored using a modified version of the National Beef Quality Audit's bruise scoring methodology (i.e., no bruise, one bruise that was ≤ the size of a deck of cards, one bruise that was > than the size of a deck of cards, and multiple bruises). Ultimate muscle pH was measured 32 to 36 hours postmortem. Multi-predictor models were selected for each outcome variable using Aikake Information Criterion (AIC). Continuous outcome variables were analyzed using linear mixed-effects models and categorical outcome variables with mixed-effects logistic regression models. Increased truck waiting time was associated with increased cortisol (P = 0.04) and lactate (P = 0.02) concentrations. Similarly, an increase in lairage duration was associated with an increase in creatine kinase (P = 0.05) and the odds of cattle being bruised (P = 0.03). Less space allowance per animal in lairage was associated with increased odds of cattle having impaired mobility (P = 0.01). There was a seasonal effect for many of the measured outcomes; the summer season was associated with greater lactate concentrations (P < 0.0001), increased odds of impaired mobility (P < 0.0001), and increased odds of carcass bruising (P = 0.003). The findings of this study indicate that many of the pre-slaughter factors assessed influence key welfare and meat quality outcomes of finished beef cattle, warranting future research and consideration.
Keywords: beef cattle; pre-slaughter management; animal welfare; transport; lairage